Enhancing Production Process Capacity for “Sang Khom Cocoa” Farmer Group, Na Ngio Subdistrict, Sang Khom District, Nong Khai Province - Khongsanthia, Chutiphong; Nakmai, Chadon; Jomwinya, Wit (Journal of Humanities and Social Sciences Thonburi University, 2022)
This research aimed to: (1) explore problems, obstacles, and capacity in cocoa production and processing; and (2) create development activity to enhance cocoa production and processing for “Sang Khom Cocoa” group, Na Ngio Subdistrict, Sang Khom District, Nong Khai Province. Data collection methods included survey, individual and group interview, participant observation, and workshop to foster knowledge, as well as monitoring and evaluation to analyze every process-i.e., upstream, midstream, and downstream—related to value chain of the group. The results indicated the “Sang Khom Cocoa” group is a grouping of cocoa farmers in Na Ngio Subdistrict. Issues and obstacles affecting the group were lack of knowledge on propagation, care and maintenance, value-added processing, access to market and consumer, as well as organizing the group structure. However, the group possessed capacity is association, capability of the group leader, propitious farmland, and the trend in agro-tourism in the area. These led to creation of activities to enhance production process capacity-i.e., knowledge training on propagation and maintenance, workshop on cocoa processing into food and cosmetics, training on finance, group structure, online marketing, as well as support on sales at events and exhibition. Significant recommendation focused on monitoring and comparison of long-term performance and outcome.